Risk perception, community myth, and practices towards COVID-19 pandemic in Southeast Ethiopia: Community based crossectional study. - Ahmednur Adem Aliyi; Musa Kumbi Ketaro; Zinash Teferu Engida; Ayele Mamo Argaw; Abduljewad Hussen Muhammed; Mesud Mohammed Hassen; Abdushekur Mohammed Abduletif; Damtow Solomon Shiferaw; Abate Lette Wodera; Sintayehu Hailu Ayene; Jeylan Kassim Esmael; Edao Sinba Etu (PLoS ONE, 2022)
Objective The objective of this study was to assess risk perception, community myths, and preventive practice towards COVID-19 among community in Southeast Ethiopia, 2020. Methods Community-based cross-sectional study was conducted among 854 participants selected using a multistage sampling technique. Data were collected using a structured questionnaire adapted from previous literature. Descriptive statistics were done to summarize the variables. A generalized linear model with binary logistic specification was used to identify factors associated with risk perception and practice. Accordingly adjusted odds ratios with 95% confidence intervals were calculated and those with p-value < 0.05 were considered as significant factors associated with risk perception and practice. Cluster analysis using a linear mixed model was performed to identify factors associated with community myth and those with p-value <0.05 were reported as significant factors associated with community myth. Results All 854 respondents gave their answer yielding 100% response rate. Of these 547 (64.1%) were male, 611 (71.5%) were rural residents, 534 (62.5%) got information about COVID-19 from TV/radio, 591 (69.2%) of them live near health facility, 265 (30.8%) have a history of substance use and 100 (11.7%) have a history of chronic illness, and 415 (48.6%) of them have a high-risk perception, 428 (50.1%) have a wrong myth about COVID-19 and 366 (42.9%) have poor practice respectively. Residence, distances from health facility and myths were significantly associated with risk perception. Occupation, knowledge, and practice were significantly associated with community myths. Also level of education, living near health facilities, having good knowledge and wrong myth were significantly associated with the practice of utilizing COVID-19 preventive respectively. Conclusion The study found high-risk perception, high wrong community myth, and relatively low utilization of available practices towards COVID-19 and factors associated with them.